The Effectiveness of Mindfulness-Based Sex Therapy on Sexual Aversion and Sexual Self-Efficacy - Ahmadzadeh , Hosna; Azadyekta , Mehrnaz; Bagheri , Fariborz (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the effectiveness of mindfulness-based sex therapy (MBST) in improving sexual self-efficacy and reducing sexual aversion among individuals experiencing sexual dysfunction. A quasi-experimental design with a pre-test, post-test, and control group was employed. The study sample consisted of 30 couples (15 in the experimental group and 15 in the control group) selected from counseling centers in Karaj. Participants in the experimental group underwent an eight-session MBST intervention, while the control group received no intervention. Data were collected using the Sexual Self-Efficacy Questionnaire (Vaziri & Lotfi, 2013) and the Sexual Desire Inventory (Ayit & Halbert, 1992), both of which demonstrated high reliability. Data analysis was performed using SPSS 24, applying multivariate analysis of covariance (MANCOVA) with repeated measures to examine within-group and between-group differences. The results revealed a significant increase in sexual self-efficacy in the experimental group compared to the control group (p < 0.001), with mean scores rising from 8.73 in the pre-test to 14.77 in the post-test. Additionally, a significant reduction in sexual aversion was observed in the experimental group, with mean scores decreasing from 50.93 in the pre-test to 44.03 in the post-test (p < 0.001). Follow-up assessments indicated that these improvements were maintained over time, while no significant changes were observed in the control group. The findings suggest that MBST is an effective intervention for enhancing sexual self-efficacy and reducing sexual aversion. The results highlight the importance of mindfulness-based approaches in addressing sexual dysfunction, providing evidence for their integration into clinical practice and sex therapy. Future research should explore the long-term effects of MBST and its applicability to diverse populations.